USING VISUALS IN TEACHING ENGLISH - Shakhodat Rakhmatullaeva Quranbay qizi (Research Focus International Scientific Journal, 2024)
Visual aids serve as powerful tools in foreign language education, offering teachers an effective means to convey complex information, introduce variety in class activities, and engage students more deeply. The advantages of incorporating visuals in language instruction are manifold, encompassing attention retention, motivation, and improved information retention. This paper delves into the theoretical underpinnings and practical applications of utilizing visual aids in the English language classroom, shedding light on their significant contribution to the learning process.